1995
DOI: 10.1111/j.1600-051x.1995.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of irrigation with chlorhexidine or saline on plaque vitality

Abstract: 24 adult patients suffering from Adult periodontitis were assigned to 4 groups: the 1st rinsed for 1 min with 0.2% chlorhexidine gluconate (CHX); the 2nd group were irrigated for 15 s with 0.2% CHX in a pulsed oral irrigator; the 3rd group rinsed for 1 min with saline and the 4th group were irrigated for 15 s with saline. Plaque vitality was measured after the 4 experimental procedures, using the method described by Netuschil et al. and scored using the method described by Rundegren et al. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
2
2
0
2
Order By: Relevance
“…In the present study, the mean difference of PI values between the three groups at the end of one-month revealed that 0.2% CHX group had the highest value of 0.9175 and 0.75% BA group had the least value of 0.4705 and this difference was statistically significant (p value=0.006). These results were similar to other research by Walsh et al and Mohammadi and Abbot [17,18]. The superior effect of CHX can be attributed to its substantive nature which helps maintain a potent sustained release and ability to help inhibit adherence of microorganisms to a surface thereby, preventing growth and development of biofilms [17,18].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the mean difference of PI values between the three groups at the end of one-month revealed that 0.2% CHX group had the highest value of 0.9175 and 0.75% BA group had the least value of 0.4705 and this difference was statistically significant (p value=0.006). These results were similar to other research by Walsh et al and Mohammadi and Abbot [17,18]. The superior effect of CHX can be attributed to its substantive nature which helps maintain a potent sustained release and ability to help inhibit adherence of microorganisms to a surface thereby, preventing growth and development of biofilms [17,18].…”
Section: Discussionsupporting
confidence: 90%
“…Beside conventional scalers and curettes, ultrasonic systems are commonly used for the removal of subgingival calculus and bacterial plaque [6]. Bactericidal chemicals as Chlorhexidine digluconate are useful adjuncts in the treatment of periodontitis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Preprocedural rinse such as chlorhexidine (CHX) in varying concentrations, are being used to reduce the bacterial contamination before ultrasonic scaling and periodontal surgery. Chlorhexidine with a dilution of 0.2% is highly effective in inhibiting subgingival plaque formation and hence prevents development of gingivitis [21]. Chlorhexidine is a cationic bisguanide molecule which can strongly bind to the hydroxyappetite, the organic pellicle of the tooth, oral mucosa, salivary protein and bacteria thereby exhibiting superior substantivity in the oral cavity [22].…”
Section: Meanmentioning
confidence: 99%